2004
DOI: 10.1016/j.ijdevneu.2004.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca2+‐independent phospholipase A2 and n−3 polyunsaturated fatty acid docosahexaenoic acid in prostanoid production in brain: perspectives for protection in neuroinflammation

Abstract: Various diseases of the central nervous system are characterized by induction of inflammatory events, which involve formation of prostaglandins. Production of prostaglandins is regulated by activity of phospholipases A(2) and cyclooxygenases. These enzymes release the prostaglandin precursor, the n-6 polyunsaturated fatty acid, arachidonic acid and oxidize it into prostaglandin H(2). Docosahexaenoic acid, which belongs to the n-3 class of polyunsaturated fatty acids, was shown to reduce production of prostagla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 72 publications
2
55
0
Order By: Relevance
“…sPLA 2 activation requires a much higher Ca 2 + concentration, 16-18 mM, and is involved mainly in the presynaptic release of synaptic vesicles (Dennis, 1994;Matsuzawa et al, 1996;Wei et al, 2003). iPLA 2 is Ca 2 + -independent and selective for DHA acid rather than AA (Dennis, 1994;Strokin et al, 2004). The chronic LiCl diet of this study is reported to reduce global brain mRNA, protein and activity levels of cPLA 2 in rats, but not to affect expression of sPLA 2 or iPLA 2 (Bosetti et al, 2002a, b;Chang and Jones, 1998;Rapoport and Bosetti, 2002;Rintala et al, 1999;Weerasinghe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sPLA 2 activation requires a much higher Ca 2 + concentration, 16-18 mM, and is involved mainly in the presynaptic release of synaptic vesicles (Dennis, 1994;Matsuzawa et al, 1996;Wei et al, 2003). iPLA 2 is Ca 2 + -independent and selective for DHA acid rather than AA (Dennis, 1994;Strokin et al, 2004). The chronic LiCl diet of this study is reported to reduce global brain mRNA, protein and activity levels of cPLA 2 in rats, but not to affect expression of sPLA 2 or iPLA 2 (Bosetti et al, 2002a, b;Chang and Jones, 1998;Rapoport and Bosetti, 2002;Rintala et al, 1999;Weerasinghe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All have been identified in neurons (Kishimoto et al, 1999;Strokin et al, 2004;Yang et al, 1999;Yegin et al, 2002). cPLA 2 has been localized at postsynaptic neuronal membranes in the brain (Basavarajappa et al, 1998;Ong et al, 1999;Pardue et al, 2003) and is activated by 300 nM to 1 mM Ca 2 + (Clark et al, 1995), in the physiological range of intracellular Ca 2 + during neuronal activation (Ismailov et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59] Like AA, docosahexaenoic acid (DHA; 22:6nÀ3; Figure 2) is esterified in the sn-2 position of brain phospholipids. It is released by a PLA 2 (most likely iPLA 2 ), [60][61][62][63] and the majority is then reesterified into brain phospholipids, while a portion of the non-esterified DHA can be converted to docosanoids which along with DHA, play important roles in brain signaling, 64 anti-inflammation 65 and neuroprotection. 36 The actions of DHA and the docosanoids are generally antagonistic to AA and its eicosanoid derivatives, respectively.…”
Section: Overview Of the Aa Cascadementioning
confidence: 99%
“…DHA is mainly released by calcium-independent phospholipase A 2 (iPLA 2 ) with a more limited regulation by calcium-dependent phospholipases A 2 in rat astrocytes. 11,12 AA is mainly released by calcium-dependent cytosolic phospholipase A 2 (cPLA 2 ) and secretory phospholipase A 2 (sPLA 2 ), 13,14 explaining how metabolic AA and DHA regulation can be independent in the brain. 15 Studies indicate that there is cross-talk between cPLA 2 and sPLA 2 and that their expression and activity are interdependent.…”
Section: Introductionmentioning
confidence: 99%